Optical Characteristics Of Nano-Talc/TiO2 Thin Layer ; A Preliminary Study - Vitrini, Nora; Jonuarti, Riri; Ratnawulan; Hidayat, Rahmat (Department of Physics, Universitas Negeri Padang, 2024)
This study tested the effect of 50%:50% concentration nano-Talc/TiO2 on optical and photocatalytic properties thin layer activity. The goal is to understand how 50%:50% concentration affects absorption, reflection and transmission as as well as photocatalytic activity of thin layer. This research is experimental, starting with grinding Talc and TiO2, followed by dilution layer synthesis using the spin coat technique. Characterization includes cross-section morphology analysis using SEM, absorption, reflection, transmission and energy measurements slit with a UV-Vis DR spectroscope, as well as photocatalytic activity test. The research results show that the coating process managed to increase absorption by (92-98)% and energy band gap of 2.93 eV while reflection and transmission are reduced by (0.5-4)%, as well as the lowest rate of photocatalytic activity degradation rate of 0%, causing low ROS under light sunlight protective layer.